Avaliação da fruta do milagre (Synsepalum dulcificum Shumach. & Thonn. Daniell) e sua glicoproteína miraculina para novas aplicações biotecnológicas - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The miracle fruit (Synsepalum dulcificum) contains a glycoprotein called miraculin, which binds to taste receptors and induces the perception of sweetness in response to acidic pH. This work aims to determine the biotechnological potential of the bioactive compounds present in the miracle fruit (Synsepalum dulcificum). The fruits were purchased from the Agroecology Reference Center, located at IFAM, CMZL campus. Biometric and physicochemical analyses were performed following the procedures described by the Adolfo Lutz Institute, considering the following parameters: pH, moisture, ash, proteins, lipids, carbohydrates, total soluble solids (TSS), total titratable acidity (TTA) and vitamin C (quantified by the reduction of cupric ions). Minerals were determined by energy-dispersive X-ray fluorescence (EDXRF). Total phenol contents were measured by the Folin-Ciocalteu method, while total flavonoids were quantified using quercetin as a standard. Antioxidant capacity was evaluated by DPPH and ABTS methods in aqueous extracts obtained at cold (ExtA/EF) and hot (ExtA/EQ). Cytotoxicity was tested against the normal MRC5 cell line using the Alamar Blue method. Miraculin present in the pericarp, both at the semi-ripe and mature stages, was purified by immobilized metal ion layer chromatography (IMAC) with Ni-NTA agarose. Miraculin quantification was done by fluorescence using Qubit. The gross mass of the fruit was 1.4 g, with the average pericarp weight being 1.1 g. The longitudinal and transverse sizes were 19.5 mm and 10.4 mm, respectively. The bioactive presented a yield of 19.9% and a moisture content of 8.25%. The centesimal composition revealed the following contents: moisture (81.03%), ash (2.35%), lipids (6.02%), proteins (4.02%) and carbohydrates (6.58%), with an average caloric value of 96.5 kcal/100 g. The pH of the fruit was 3.39, with ATT of 3.36% and SST of 13.77 °Brix. The concentration of vitamin C in the lyophilized pericarp was 12.9 mg/100 g ± 0.02. The element with the highest mass concentration identified was K with 165.91 mg/100g, followed by Ca with 26.56 mg/100g, Fe (20.45 mg/100g), S (7.52 mg/100g), P (5.88 mg/100g), Cr (3.29 mg/100g), Si (2.59 mg/100g), Rb (1.65 mg/100g), and Zn (1.18 mg/100g). The results for total phenols were 3.1% for EXTA/EF and 3.7% for ExtA/EQ, with no statistically significant difference. As for total flavonoids, ExtA/EF presented 0.7%, significantly higher than ExtA/EQ, with 0.6%. The antioxidant capacity, measured by the DPPH method, did not present significance, with values of 40.2% for EXTA/EF and 37.7% for ExtA/EQ. However, using the ABTS method, ExtA/EF obtained 55.3%, a significantly higher value than ExtA/EQ, which presented 36.3%. The IC50 of ExtA/EF, using the ABTS method, was 89.6%. No cytotoxicity was observed in the pericarp. Miraculin levels were 0.203 mg/mL at the semi-ripe stage and 0.232 mg/mL at full ripeness. Therefore, the study concluded that the miracle fruit (Synsepalum dulcificum) is a source of vitamin C for adult women, with potassium as the main element. The aqueous extract obtained by cold extraction (ExtA/EF) was found to be the most effective for obtaining flavonoids with high antioxidant potential. Miraculin was more abundant in ripe fruits, and the fruit showed no cytotoxicity. These results highlight its potential for biotechnological applications, such as pharmaceuticals, cosmetics, and dietary supplements with sweetening properties.
Keywords: Frutas - Compostos bioativos; Synsepalum; CIENCIAS BIOLOGICAS; Miraculina; Receptores gustativos; Modificador de sabor; Extração